Joint Works Production Committees - TUC leaflet, 1942 (1942)
1942 1939-1945 "Joint Works Production Committees - TUC leaflet, 1942" [HFR0088], 1942 During 1942, a number of conferences took place between the TUC and engineering unions and employers to discuss the introduction of joint production consultative machinery in workplaces and districts. By the end of 1943, over 4000 Joint Works Production Committees had been established in the engineering and shipbuilding industries to resolve any issues arising from the Essential Works Orders issued from 1941 which might disrupt production.